Perhitungan Harga Pokok Produksi menggunakan Metode Full Costing untuk menentukan Harga Jual - Sakti, Tamaarine Ayunillah Afraaniti; Ishak, Jouzar Farouq; Arief, Khozin; Supriatna, Iyeh (Indonesian Accounting Literacy Journal, 2025)
This research was conducted at the Toko Lis Collection which is included in the manufacturing business category. This study aims to determine the-cost of production carried out by the Toko Lis Collection, using-the full costing method. The research method used is descriptive analysis method with data collection techniques using interview and documentation technique. The sample used in this study was taken from a production sample in May 2023 of 485 units. The results of this study show that the calculation of the cost of production carried out by the Toko Lis Collection and calculations using the full costing method have differences that cause differences in the determination of the selling price. The result of calculating the cost of production according to the company Rp 34.000/unit with selling price of Rp 55.000/unit, while the calculation of the cost of production using the full costing method is Rp 36.448/unit with a selling price of Rp 59.045/unit.